ERICH FROMM AND HIS CONCEPTION OF THE FREEMAN - Ikrom Jomuradov (European Science Publishing, 2024)
In the article is exposed E. Fromm's and F. Nietzsche understanding of the problem of human's alienation in society and are provided the ways to overcome it. Philosophers considered types of freedom and mechanisms o escape from freedom.
Keywords: man, the accomplishment of man, the individual, society, negative freedom, positive freedom, spontaneous activity, love.